FRIEDMAN'S ANALYSIS OF THE READING LITERACY PROGRAM IN IMPROVING STUDENT'S READING SKILLS - Pitri, Rizka Pitri; Alvionita, Elisya (Parameter: Journal of Statistics, 2025)
The School Literacy Movement (GLS) is an effort to cultivate character through reading activities. GLS becomes the foundation of the learning process through the establishment of a school culture as a comfortable learning environment and leads to increased literacy skills in students. One of the School Literacy Movement is the 15-minute reading program before learning begins which is implemented in education units. However, the GLS program has not been comprehensively based on the GLS guidelines from MoEC-Ristek. The intensity of GLS activities is still lacking because it is only done twice a week. Based on this fact, the researcher conducted a 15-minute reading program before learning begins four times a week. This study aims to evaluate the implementation of the reading literacy program in improving reading skills. The samples in this study were early grades I and II of MIN 3 Bandar Lampung. This study used quantitative methods by applying Friedman and Effect Size analysis. This study found that there is a difference in the level of reading skills before and after the implementation of the 15-minute reading program before learning begins, in other words, the program has effectiveness in improving reading skills. The effectiveness of the 15-minute reading literacy program before learning begins on improving the reading skills of early grade students is 0.7 or equivalent to 76% effectiveness.